2019
DOI: 10.4081/or.2019.7989
|View full text |Cite
|
Sign up to set email alerts
|

Insurance status affects access to physical therapy following rotator cuff repair surgery: A comparison of privately insured and Medicaid patients

Abstract: Rotator cuff repair (RCR) is an effective procedure to relieve shoulder pain and dysfunction. Postoperative physical therapy (PT) plays an integral role in the overall success of RCR. Insurance status has been shown to be an important predictor of postoperative PT utilization. This study evaluated the effect of insurance status on access to PT services following RCR. One hundred thirty-eight PT clinics were contacted in the Greater Boston metropolitan area. Clinics were contacted on two separate occasions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Patterson et al 6 found that the likelihood of being able to make an appointment for PT to manage an acute rotator cuff tear in North Carolina was 8.8 times higher (95% CI: 2.5%-31.5%) for patients who were privately insured compared with patients with Medicaid insurance. Similarly, Rogers et al 7 found that in the Greater Boston Area, only 51.4% of practices accepted Medicaid insurance, while 96.4% accepted private insurance ( P = .02) for PT appointments after RCR. This is similar to the national acceptance rates we have found in this study with only 52.7% of practices accepting Medicaid vs. 94.9% accepting private insurance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Patterson et al 6 found that the likelihood of being able to make an appointment for PT to manage an acute rotator cuff tear in North Carolina was 8.8 times higher (95% CI: 2.5%-31.5%) for patients who were privately insured compared with patients with Medicaid insurance. Similarly, Rogers et al 7 found that in the Greater Boston Area, only 51.4% of practices accepted Medicaid insurance, while 96.4% accepted private insurance ( P = .02) for PT appointments after RCR. This is similar to the national acceptance rates we have found in this study with only 52.7% of practices accepting Medicaid vs. 94.9% accepting private insurance.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study evaluating access to PT services after RCR in the Greater Boston Area found that only 51.4% of PT practices accepted Medicaid as compared with 96.4% accepting private insurance. 7 Among those practices accepting Medicaid insurance, Medicaid patients experienced significantly longer wait times as compared with privately insured patients. This finding is particularly concerning as Massachusetts has one of the most robust Medicaid expansion plans in the United States.…”
mentioning
confidence: 99%
“…It is important to underscore the close relationship between access and outcome for rotator cuff repair. In studies by Rogers, et al 44 , and Patterson, et al 39 , Medicaid patients experienced longer wait times for appointments for physical therapy and orthopedic consult, respectively. Additionally, patients in Curry, et al 12 , were offered fewer appointments for care.…”
Section: Discussionmentioning
confidence: 96%
“…Further, worse postoperative outcomes associated with low SES persist in orthopedic surgeries, such as total joint arthroplasties 13,59 and spine surgery 31,35 . Several studies observe similar trends in care for rotator cuff tear 8,12,24,30,39,44,48 .…”
mentioning
confidence: 83%
See 1 more Smart Citation